Forecasting the effects of climate change on the climatic of the Miahne-city using climate models (SDSM) - anoshiravan ravand; shahriar khaledi; davod hasanabadi (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study is to determine and predict the effects of climate change on architecture using climate models. By clarifying the consequences of the impact of urban architecture on climate change while using the data of surrounding stations with library and field data methods. The climatic parameters of precipitation, temperature and relative humidity of the synoptic station of Miyaneh city during a full period of 32 years (2018-1987) and the possibility of climate change with the models in this city were examined and after obtaining the relevant data Climate change was predicted for the next 84 years through the GCM and SDSM microscale and the AR4 (2007) - HADCM3 (Run 1) - SR-A2 scenarios. In order to evaluate the effects of climate change on the comfort climate of the region, among the bioclimatic models used, the Tarjong model was considered for two periods of 16 and 42 years. In the next 84 years, compared to the last 32 years, the cold months of May, June, July and August will turn into pleasant heat, and in September, the heat will have a great impact on the skin, which indicates a warm climate in the next 84 years. Architectures must be considered.